Internet users’ participation and news framing: the Strauss-Kahn case-related Live Blog at Le Monde.fr - Marty, Emmanuel; Pignard-Cheynel, Nathalie; Sebbah, Brigitte (My University, 2017)
This article analyses Internet users’ participation and the ways in which it is framed by journalists, with a particular focus on the Live Blog format. It provides a case study of the online media coverage of Dominique Strauss-Kahn’s arrest in New York in May 2011, by the highly respected media Le Monde.fr. A lexicometric (statistical) and discourse (qualitative) analysis of two sets of corpora (Corpus 1 being composed of all the comments submitted by Internet users throughout the live blogging process and Corpus 2 of the few which were finally published on the Live Blog) will highlight the nature and the various forms of audience participation as well as the ways in which they are framed by journalists. The article aims to investigate the representativeness of the published messages and the participative audience profile which journalists foreground within this media space of multiple voices.
Keywords: Digital journalism; journalistic norms; lexicometric analysis; live blogging; media framing; participatory journalism; public